Craniocaudal tumour extension in uterine cervical cancer on MRI compared to histopathology. (2015) - de Boer, Peter; Bleeker, Maaike C.G.; Spijkerboer, Anje M.; van de Schoot, Agustinus J.A.J.; Bipat, Shandra; Buist, Marrije R.; Rasch, Coen R.N.; Stoker, Jaap; Stalpers, Lukas J.A.
Highlights: Median craniocaudal extension of uterine cervical cancer on MRI is systematically slightly smaller compared to histopathology (2.1 vs. 2.5 cm). Pearson's correlation: 0.83 ( p < 0.001). Regarding the craniocaudal extension on MRI, 91% (19/21) of the extension would have been covered by a clinical uncertainty margin of 1.2 cm. Comparison of tumour measurements on MRI and surgical specimen is hampered by organ deformation. However, this methodological limitation might be solved by use of deformable image registration. Abstract: Purpose: To assess the reliability of magnetic resonance imaging (MRI) for evaluation of craniocaudal tumour extension by comparing the craniocaudal tumour extension on the pre-operative MRI and post-operative hysterectomy specimen in patients with early stage uterine cervical cancer. Materials and methods: After approval of the institutional review board was acquired, pre-operative MRI and hysterectomy specimen of 21 women with early stage cervical cancer were re-evaluated. The craniocaudal extension on MRI was measured separately by two experienced radiologists and compared with corresponding measurements from the hysterectomy specimen, which were re-evaluated by an experienced pathologist. Results: Median craniocaudal extension of uterine cervical cancer on MRI was slightly smaller compared to histopathology (2.1 cm vs. 2.5 cm). The median underestimation was 0.4 cm (range −0.6 cm to 2.2 cm, mean 0.4 cm, standard deviation (SD) ±0.7 cm); Pearson's correlation was 0.83 ( p < 0.001). In two patients (9%) MRI underestimated tumour craniocaudal extension by more than 1.8 cm. Conclusion: MRI represents the histopathological craniocaudal tumour extension in the majority of patients with early stage uterine cervical cancer, but with a systematic small underestimation of the real craniocaudal tumour extension.